Amphetamine-type stimulant use and conditional paths of consumption: data from the Second Brazilian National Alcohol and Drugs Survey - Luciana T.S. Massaro; Renata R. Abdalla; Ronaldo Laranjeira; Raul Caetano; Ilana Pinsky; Clarice S. Madruga (Brazilian Journal of Psychiatry, 2017)
Objective: The aim of this study was to estimate nationally representative prevalence rates of amphetamine-type stimulant (ATS) use and to identify consumption-associated factors, proposing a conditional model of direct and indirect consumption paths. Method: Using data from the Second Brazilian National Alcohol and Drugs Survey, this cross-sectional study analyzed a subsample of 3,828 participants between 15 and 64 years old, gathering information on the use of psychoactive substances in a probabilistic sample of the Brazilian household population. Results: Rates of lifetime and last-year ATS use were, respectively, 4.1 and 1.6%. Economically privileged individuals and users of other substances were more at risk for using ATS. The results suggest that higher education decreases the chances of ATS consumption. The conditional model showed that higher income increased ATS use, higher education lowered the odds of such an increase, and cocaine use cancelled that associative effect. Conclusion: Brazil presents high rates of ATS use. Prevention and treatment strategies should focus on the protective effect of higher education levels and should target polydrug use. Knowledge of ATS-associated factors and user profiles is the starting point for developing effective treatments and tailored prevention strategies.